2012
DOI: 10.1002/lary.22458
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal mask airway versus endotracheal tube in pediatric adenotonsillectomy

Abstract: Use of the LMA during pediatric tonsil surgery does not appear to have any major disadvantages compared to use of the ETT. In fact, analysis of safety, comfort, complications, and postoperative problems suggests that LMA may be superior for some outcome variables such as coughing and gagging. Use of spontaneous ventilation is more common among LMA patients, although the significance of this finding is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 18 publications
2
43
1
Order By: Relevance
“…Ali CA et al [2] found that there was more coughing after extubation (ETT-17%, FLMA-5.7%), than after withdrawal of the FLMA. A study by DI Sierpina et al [20] demonstrated that, ETT use was associated with more coughing (48% for ETT and 20% for FLMA). Punkaj Kundra et al [19] had reported an increased incidence of persistent cough in the ETT group (36% ETT vs 15% FLMA).…”
Section: Discussionmentioning
confidence: 99%
“…Ali CA et al [2] found that there was more coughing after extubation (ETT-17%, FLMA-5.7%), than after withdrawal of the FLMA. A study by DI Sierpina et al [20] demonstrated that, ETT use was associated with more coughing (48% for ETT and 20% for FLMA). Punkaj Kundra et al [19] had reported an increased incidence of persistent cough in the ETT group (36% ETT vs 15% FLMA).…”
Section: Discussionmentioning
confidence: 99%
“…The safety and efficacy of SGA use in pediatric patients is well established, for both the spontaneously breathing child and those requiring positive pressure ventilation of the lungs. Surgeries that have traditionally been accomplished with endotracheal tubes, such as adenotonsillectomies and laparoscopic procedures, have been safely done with SGAs . A recent study showed that SGA use in infants actually resulted in less perioperative respiratory adverse events compared with endotracheal intubation .…”
Section: Background Of Sga Use In Clinical Practice Todaymentioning
confidence: 99%
“…Its shape is adjusted by body temperature and closes pharynx and its surroundings without any damage. LMA length is selected based on the patient's weight (Eschertzhuber , 2009;Saraswat ., 2011;Cook & Kelly, 2015;Sierpina ., 2012; 10. R u s s o ., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…R u s s o ., 2012). However, till date LT has not been studied well (Mathis ., 2013;Sierpina ., 2012;Russo , 2012). Nevertheless, those studies which analyzed LT had always resulted contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation